Nonlinear Look-Up Table Predistortion and Chromatic Dispersion Precompensation for IM/DD PAM-4 Transmission - Pengqi Gou; Li Zhao; Kaihui Wang; Wen Zhou; Jianjun Yu (IEEE Photonics Journal)
In this paper, we propose and experimentally demonstrate 10 GBaud intensity modulation direct detection pulse amplitude modulation 4 transmission over 48-km single mode fiber (SMF). Look-up table predistortion and chromatic dispersion precompensation are employed to mitigate channel bandwidth constraint and nonlinear impairment. At the receiver side, decision-directed least mean square and cascaded multimodule algorithm are employed to improve the decision precision. By combining these techniques, link budgets of 5.3 and 4 dB are achieved at bit error rate of 1 × 10−3 for the back-to-back case and after transmission over 48-km SMF, respectively.